Analisis Pertumbuhan Laba Pada Sub Sektor Perbankan: Bukti Empiris Bursa Efek Indonesia - Diah Hayuningtyias; Dhani Ichsanuddin Nur (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Profit growth is a measure of the company's ability to increase net profit from year to year. The purpose of this study is to examine and analyze the effect of Debt to Equity Ratio, Current Ratio, Total Assets Turnover and company size on profit growth in banking sub-sector companies listed on the Indonesia Stock Exchange during 2017-2020. The population of this study were 43 companies and the sample contained 24 companies that met the criteria. The sampling method was carried out by purposive sampling method. This study uses multiple linear regression data analysis methods, classical assumption test (normality test, multicollinearity test, heteroscedasticity test, auto correlation test), hypothesis test (t test, f test, coefficient of determination. The results show that the Debt to Equity Ratio can contribute to profit growth, Current Ratio can contribute to profit growth, Total Assets Turnover can contribute to profit growth, and Company size can contribute to profit growth